Eksistensi perpustakaan di era teknologi - Mrs Nurtakyidah (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2017)
This article discusses about The existence of libraries in the technological era. basically between the library and the community need each other. That is, the library will exist and exist if needed by the community. In contrast, libraries also have an interest in providing services to the public. Therefore, libraries always try to give the best as far as possible and possible. An effort that provides immediate benefits to the community in addition to the mobile library can be reached through the provision of book donation packages, village entrance library, wakaf book movement, the establishment of community reading parks, reading houses and the establishment of community learning centers.Keywords: services, search, information Technology